Effects of Orthodontic Treatment on Patients' Dental Anxiety and Oral Health Knowledge - Fırat Öztürk; Oral Sökücü; Serhat Demirer; Ruhi Nalçacı; Hakan Özdemir (Galenos Yayinevi, 2009)
The aim of this study was to investigate effects of orthodontic treatment on both anxiety and oral health knowledge of orthodontic patients. The study was carried out in 184 patients. Four groups were formed according to the stage of orthodontic treatment. Group 1 consisted of 47 individuals selected from patients who were awaiting orthodontic treatment; groups 2 and 3, comprised 44 and 46 individuals who had been undergoing orthodontic treatment for a period of 1-12 and 12-26 months respectively, and group 4, 47 orthodontically treated individuals. The modified Dental Anxiety Scale was used to measure dental anxiety. Oral health knowledge was assessed using several questions concerning etiology, symptoms and prevention. Chi-squire test was used for statistical assessment. The anxiety level of patients in group 1 was significantly higher than the subjects in group 4. Patients in groups 2, 3 and 4 mostly knew that gum bleeding is a sign of periodontal disease (81.8, 84.7, 80.1 per cent respectively); and this was 63.8 per cent for group 1. Patients in all groups were aware how to prevent, however those who were undergoing or had completed treatment were more informed about symptoms of periodontal disease. Only 19.6 and 52.1 per cent of subjects in group 3 had the knowledge to identify dental plaque and what it can cause respectively; which was the highest ratio among the groups. Orthodontic treatment involves some degree of exposure, consequently creates a positive influence on patients' anxiety and periodontal health knowledge.